Prevention of foot ulcers in the at-risk patient with diabetes: a systematic review - Tricia Price (Diabetes/Metabolism Research and Reviews, 2016)
BackgroundPrevention of foot ulcers in patients with diabetes is extremely important to help reduce the enormous burden of foot ulceration on both patient and health resources. A comprehensive analysis of reported interventions is not currently available, but is needed to better inform caregivers about effective prevention. The aim of this systematic review is to investigate the effectiveness of interventions to prevent first and recurrent foot ulcers in persons with diabetes who are at risk for ulceration.MethodsThe available medical scientific literature in PubMed, EMBASE, CINAHL and the Cochrane database was searched for original research studies on preventative interventions. Both controlled and non‐controlled studies were selected. Data from controlled studies were assessed for methodological quality by two independent reviewers.ResultsFrom the identified records, a total of 30 controlled studies (of which 19 RCTs) and another 44 non‐controlled studies were assessed and described. Few controlled studies, of generally low to moderate quality, were identified on the prevention of a first foot ulcer. For the prevention of recurrent plantar foot ulcers, multiple RCTs with low risk of bias show the benefit for the use of daily foot skin temperature measurements and consequent preventative actions, as well as for therapeutic footwear that demonstrates to relieve plantar pressure and that is worn by the patient. To prevent recurrence, some evidence exists for integrated foot care when it includes a combination of professional foot treatment, therapeutic footwear and patient education; for just a single session of patient education, no evidence exists. Surgical interventions can be effective in selected patients, but the evidence base is small.ConclusionThe evidence base to support the use of specific self‐management and footwear interventions for the prevention of recurrent plantar foot ulcers is quite strong, but is small for the use of other, sometimes widely applied, interventions and is practically nonexistent for the prevention of a first foot ulcer and non‐plantar foot ulcer.